A comparison of approximate models for radiation in gas turbines. (12th May 2004) - Frank, M.; Seaid, M.; Klar, A.; Pinnau, R.; Thommes, G.; Janicka, J.
Approximate equations for radiative heat transfer equations coupled to an equation for the temperature are stated and a comparative numerical study of the different approximations is given. The approximation methods considered here range from moment methods to simplified PN-approximations. Numerical experiments and comparisons in different space dimensions and for various physical situations are presented.